Towards Sustainable Freight Logistics in Desert Australia: A Framework for Analysing Options that Meet Economic, Environmental and Social Demands - Ireland, Marnie; Rola-Rubzen, Maria Fay; Callender, Guy (European Business School, 2009)
Establishing supply chains to improve delivery of goods and to source Aboriginal produce and on-sell products from remote communities offers significant opportunities for sustainable development and improved liveability in remote communities. It also forces a revision of what constitutes efficient freight logistics in desert areas. In addressing challenges for freight services in Desert Australia the main research objective is to develop a methodology for evaluating current freight logistics using a set of metrics incorporating economic, environmental and social parameters. The structure of existing freight logistics models (generally based on algorithms of time, distance and cost) does not allow for the incorporation of environmental and social elements into an evaluation, and the relevant literature demonstrates the shortcomings of this. Consequently, the paper outlines an extension of the Balanced Scorecard (ESC) approach to performance management (Kaplan & Norton, 1992). The interrelationship of the four existing perspectives contained within this multi-dimensional performance measurement (MDPM) model have been extended to include social and environmental aspects.